A maturing market : the Iberian book world in the first half of the seventeenth century - Wilkinson, Alexander S., 1975-; Ulla Lorenzo, Alejandra (Library of the written word ;, 2017)
Within just a generation or two of its arrival, print had become a ubiquitous and spirited part of Spain and Portugal's urban cultures. It serviced an ever-expanding reading public, as well as many and varied practical quotidian needs. Its impact on society was multi-dimensional and complex, and its social reach far broader than the civic or ecclesiastical elites were ever to be entirely comfortable with. This cross-disciplinary volume of essays focuses on the maturing marketplace for print in the first half of the seventeenth century, shedding new light on some important transformations, with authors and publishers seizing opportunities available to them - negotiating the regulatory efforts of the censors, and scrambling to reconfigure their relationship with their readers.